Facultative oviparity in a viviparous skink (Saiphos equalis) - Laird, Melanie K. (Biol Lett, 2019)
Facultative changes in parity mode (oviparity to viviparity and vice versa) are rare in vertebrates, yet offer fascinating opportunities to investigate the role of reproductive lability in parity mode evolution. Here, we report apparent facultative oviparity by a viviparous female of the bimodally reproductive skink Saiphos equalis—the first report of different parity modes within a vertebrate clutch. Eggs oviposited facultatively possess shell characteristics of both viviparous and oviparous S. equalis, demonstrating that egg coverings for viviparous embryos are produced by the same machinery as those for oviparous individuals. Since selection may act in either direction when viviparity has evolved recently, squamate reproductive lability may confer a selective advantage. We suggest that facultative oviparity is a viable reproductive strategy for S. equalis and that squamate reproductive lability is more evolutionarily significant than previously acknowledged.